Stereotypes Determining Perceptions of Female Politicians: The Case of Poland - Turska-Kawa Agnieszka (Sciendo, 2018)
The aim of this study is to find out whether women in Polish politics are perceived through the prism of gender stereotypes. We conducted a two-stage empirical study (N=447) to investigate the kinds of qualities that young voters attribute to politicians in the context of gender stereotypes. Our findings correlated with a pattern of research that shows that female politicians are typically associated with “female issues” and seen in terms of stereotypically feminine traits. The results of our survey showed gender solidarity, with female and male participants generally responding more positively to politicians of the same gender. There were also significant differences based on respondents’ interest in politics; people interested in politics were, for example, significantly less likely to ascribe qualities related to political ability and self-composure to women. Finally, ideological identifications did not modify perceptions of female politicians but people who identified as right-wing more often viewed male politicians as politically capable, diligent, likeable and go-getters.